Qatari policy towards resolving border disputes with Saudi Arabia 1913-1992 - Alhamadi, Mariam; Banisalman, Mohammad (Dirasat: Human and Social Sciences, 2021)
The current study highlights the policy adopted by the State of Qatar in dealing with disputes over delineation of its borders with Saudi Arabia. This goal was achieved by investigating the problem of border issues and its root causes in the Gulf region in general and between Qatar and Saudi Arabia in particular. The British stance on these issues is then reviewed, and finally, the study traces the Qatari policy adopted in resolving these problems and the consequences thereof. This was achieved by an evaluation of all procedures followed be they diplomatic, legal, or military. The study concludes that the problem of demarking borders is common between the different Gulf States and Qatar is not different in this respect. The British stance was often characterized by bias or ambiguity based on its interests in the region. Furthermore, it is concluded that the Qatari policy in handling border issues with neighboring countries primarily focused on diplomatic and legal channels, but Qatar did not hesitate to use force or threaten to opt for it when deemed necessary.